Augmenting Multi-Agent Environment Descriptions with a Normative Infrastructure - Okuyama, Fabio Y.; Bordini, Rafael H.; Costa, Antônio Carlos da Rocha (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2007: Anais do VI Encontro Nacional de Inteligência Artificial, 2007)
This paper presents an approach for the development of environments for situated multi-agent systems. The approach includes features that allow designers to associate organisational structures to the environment. Spatially distributing the normative information over the environment is a natural way to simplify the definition of organisational structures and the development of large-scale multi-agent systems. By distributing the normative information in different spatial locations, we allow agents to directly access the relevant information needed in each environmental context.